Source out, risk in [offshore software development]. - Frank, S.J.
This paper discusses how offshoring software development projects from the US, particularly those involving software programming and information technology, can put intellectual property (IP) at risk. Without reliable institutions for IP enforcement, outsourcers must place their faith in prevention rather than cure. However, even the best safeguards can never guarantee invulnerability. The ideal self-help strategy, therefore, extends beyond prevention and assumes that bad things will happen.
Keywords: IP theft; Intellectual property; Offshoring software development